Bioaccumulation of metals in sediment elutriates and their effects on growth, condition index, and metallothionein contents in oyster larvae - Geffard, A.; Geffard, Olivier; Amiard, J.C.; His, E.; Amiard Triquet, C. (Archives of Environmental Contamination and Toxicology, 2007)
[Departement_IRSTEA]MA [TR1_IRSTEA]QSA / EXPER The bioavailability of Cd, Cu, Zn and Pb from two metal-contaminated sediments (Bidassoa and Dunkerque) was studied using Crassostrea gigas larvae exposed to sediment elutriates. The metal contents within the sediments, the larvae and larval growth, the condition index, and the induction of metallothionein in the larvae were measured. The larval growth and condition index were only affected after exposure to the highest elutriate concentration (5 to 25%) from the most contaminated sediment (Dunkerque). Bioaccumulation of all metals was observed in larvae exposed to Dunkerque elutriatre and; only Cu bioaccumulation was observed in the case of Bidassoa elutriate. The compilation of results from larvae exposed to both sediment elutriates show a strongly correlation between bioaccumulated metal considered individually or combined in combination and the metallothionein level in larvae presenting no detrimental effect. In contraryOn the other hand, in the case of larvae exposed to the highest Dunkerque elutriate concentration and showing the highest metal body burdens, we observed a drop of in the metallothionein level. These results indicate that metallothionein is a more sensitive indicator of heavy metal pollution, compared to than physiological endpoints takening into account in bioassays and could be proposed as precocious an early biomarker of metals exposure in larvae. However, it must be take care to themust be taken with fault control due to the toxicological effect on larvae metabolism in the case of important substantial contaminant exposure.